DESIGN AND FABRICATION OF SPLIT HELMET - Prof. Shivashankar C; Prof. Gangadhar Biradar; Salman; Syed Faizan; M. A. Faizan (International Educational Journal of Science and Engineering, 2026)
This study presents a novel design for a split helmet that is easy to manufacture and suitable for large-scale production. The helmet casing is made of carbon fiber to enhance durability, while an integrated cooling towel and adjustable ventilation system improve user comfort. A key safety feature is the foam liner, designed to absorb impact energy during accidents. The study aims to develop a motorcycle helmet with an optimized energy-absorbing liner using engineering design methods, including design of experiments and response surface modeling. The proposed helmet’s performance is evaluated through simulations and compared with existing commercial helmets, showing reduced head injury criteria and lower maximum acceleration in most impact scenarios. In addition, the study explores behavioral factors influencing helmet usage among motorcyclists, particularly in low road-safety environments. Using detailed empirical data, it is observed that risk-averse and well-informed individuals are more likely to wear helmets and adopt safer driving behaviors. Increased awareness and education significantly improve helmet usage. The findings suggest that enforcing helmet laws, promoting awareness, and improving infrastructure are essential strategies to reduce road fatalities. A helmet serves as a crucial protective device against head injuries, yet negligence and lack of awareness result in significant fatalities, especially in India. According to NCRB data, two-wheeler accidents claim numerous lives daily, often due to the absence of helmets. To address portability concerns and encourage usage, this study proposes a split helmet design that is compact and easy to carry.